Tephrostratigraphy of the Waki-Mille area of the Woranso-Mille paleoanthropological research project, Afar, Ethiopia. Issue 93 (April 2016) - Saylor, Beverly Z.; Angelini, Joshua; Deino, Alan; Alene, Mulugeta; Fournelle, John H.; Haile-Selassie, Yohannes
Abstract: Tephra geochemistry and 40 Ar/ 39 Ar geochronology are reported for the Waki-Mille area in the northwestern part of the Woranso-Mille paleoanthropological project area in the west central Afar region of Ethiopia. Previous studies documented dentognathic fossils that are morphologically intermediate between Australopithecus anamensis and Australopithecus afarensis and some that are attributed to Australopithecus afarensis . Additional dentognathic remains from the study area were assigned to the newly identified species Australopithecus deyiremeda . These fossil hominin taxa were recovered from volcanic and sedimentary strata containing tuffs ranging in age from more than 3.77 million years ago (Ma) to less than 3.469 Ma. One of the tuffs was correlated based on geochemistry, feldspar mineralogy, and age to the Lokochot Tuff of the Omo-Turkana Basin of southern Ethiopia and Kenya. Variations in major and minor element abundances in volcanic glass demarcate ten geochemically distinct tuffs and tuff sequences, including three that are geochemically similar to widespread regional tuffs, specifically the Lomogol, Lokochot, and β− Tulu Bor/Sidi Hakoma tuffs. A new 40 Ar/ 39 Ar age for the Waki Tuff, which is geochemically similar to the Lomogol Tuff, is 3.664 ± 0.016 Ma. Other tuffs in the Waki-Mille area are geochemically dissimilar to regional tuffs documented to date. Identification of tuffs based on character, stratigraphic position, and geochemistry refines local stratigraphic correlations and delineates the geographic distributions of precisely dated fossiliferous levels within the Waki-Mille area.